Ecological gradients drive insect wing loss and speciation: The role of the alpine treeline. Issue 13 (25th May 2019) - McCulloch, Graham A.; Foster, Brodie J.; Dutoit, Ludovic; Ingram, Travis; Hay, Eleanor; Veale, Andrew J.; Dearden, Peter K.; Waters, Jonathan M.
Abstract: Alpine ecosystems are frequently characterized by an abundance of wing‐reduced insect species, but the drivers of this biodiversity remain poorly understood. Insect wing reduction in these environments has variously been attributed to altitude, temperature, isolation, habitat stability or decreased habitat size. We used fine‐scale ecotypic and genomic analyses, along with broad‐scale distributional analyses of ecotypes, to unravel the ecological drivers of wing reduction in the wing‐dimorphic stonefly Zelandoperla fenestrata complex. Altitudinal transects within populations revealed dramatic wing reduction over very fine spatial scales, tightly linked to the alpine treeline. Broad biogeographical analyses confirm that the treeline has a much stronger effect on these ecotype distributions than altitude per se. Molecular analyses revealed parallel genomic divergence between vestigial‐winged (high altitude) and full‐winged (low altitude) ecotypes across distinct streams. These data thus highlight the role of the alpine treeline as a key driver of rapid speciation, providing a new model for ecological diversification along exposure gradients. Abstract : see also the Perspective by Emerson et al.